PEMFC Technology as a Mobile Generator and Back Up Power Supply Environmentally Friendly - Dwi Pamungkas, Enggik; Wahyu Kurniyanto, Fajar; Aditya Putra, Fariz; Trisa Rani Marpaung, Helena; Silvia; Priyono, Bambang (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Hydrogen as a renewable energy source is increasingly important in efforts to reduce carbon emissions and transition to clean energy. Many power plants are equipped with hydrogen plants that produce hydrogen gas continuously, but excess hydrogen is often disposed of when storage reaches maximum capacity. This study proposes the use of excess hydrogen to power fuel cells as a backup energy source in various important facilities, such as commercial centres, fitness, and health services. Hydrogen fuel cells offer the main advantage of zero-emission operation, making them an ideal solution for improving energy sustainability. By using previously discarded hydrogen, not only energy waste can be minimized, but it also opens new business opportunities in the sale and rental of fuel cell systems to consumers who care about their carbon footprint and clean energy. The hydrogen gas productivity at a power plant reaches 88.8 kg/day, and the potential excess hydrogen gas at a power plant reaches 48.84 kg/day. One kilogram of hydrogen gas can generate 15 to 20 kWh of electrical energy. The study also examines potential business models that focus on the utilization of hydrogen from renewable energy sources such as solar, hydro, and geothermal. In addition, the analysis shows that the application of fuel cells for backup energy systems in strategic locations can reduce dependence on conventional energy that generates emissions. The use of this technology has great potential to support green energy infrastructure in Indonesia and is in line with global initiatives towards reducing carbon emissions. With the cost of hydrogen production getting lower and the growing awareness of the importance of clean energy, this approach is expected to play a significant role in achieving sustainable energy targets.